Social Assessment Identifies Land Management Concerns in Cote d'Ivoire - Fisiy, Cyprian (World Bank, Washington, DC, 2012)
Rural areas in Cote d'Ivoire account for 55 percent of the total population. Rural people rely heavily on export- and food-crop production as their primary source of livelihood. However, 71 percent of the rural population live below the poverty line. The government and the Bank agree that access to land and natural resource management are critical factors in coping with the rural crisis. The government invited the Bank to help meet the rural development challenge through a new project, the Rural Land Management and Infrastructure Project (PNGTER). The project was designed as one component of a nationwide decentralization program, and it seeks to suggest new approaches for local resource management. The social assessment (SA) in this project identifies the key social development concerns: access, control, and management of land rights. This Note explains the objectives of the social assessment, the basic steps followed, and the next steps. It captures the findings of the provisional SA process at the project identification stage and raises a few new issues that need to be addressed through the SA process during the preappraisal, appraisal, and implementation stages.